1988
DOI: 10.1016/0007-1935(88)90053-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an influenza A (H3N2) virus isolated from pigs in England in 1987

Abstract: This study describes the isolation and characterization of an influenza virus subtype H3N2 designated A/Swine/Weybridge/163266/87 . The virus was isolated from a severe outbreak of respiratory disease in East Anglia . Haemagglutinin and neuraminidase characterization showed the virus to be very similar to H3N2 strains circulating in the human population during the years 1972-1975, and to H3N2 strains recently isolated from pigs in Belgium and France . A serological survey showed antibodies to the virus to be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The H3N2 infected pigs were the worst affected and did show mild respiratory symptoms (nasal discharge). Similar results have been described previously for the H3N2 strain (Wibberley et al 1988). Serial passage in embry-onated eggs might have reduced the pathogenicity of these viruses for pigs.…”
Section: Discussionsupporting
confidence: 88%
“…The H3N2 infected pigs were the worst affected and did show mild respiratory symptoms (nasal discharge). Similar results have been described previously for the H3N2 strain (Wibberley et al 1988). Serial passage in embry-onated eggs might have reduced the pathogenicity of these viruses for pigs.…”
Section: Discussionsupporting
confidence: 88%
“…This finding explains why no human viruses have been isolated from horses, while they have transmitted into pigs multiple times (10,24,29,46,51). Pig trachea contains both the SA␣2,6Gal and SA␣2,3Gal moieties (16).…”
Section: Discussionmentioning
confidence: 99%
“…Although human influenza viruses have been transmitted to pigs and vice versa (10,24,29,33,46,51), human-to-horse transmission remains to be reported. The finding of differences in sialyloligosaccharide species in tracheal epithelial cells between humans (predominantly NeuAc␣2,6Gal) and horses (predominantly NeuGc␣2,3Gal) suggested that recognition not only of SA-Gal linkages but also of SA species may be responsible for lack of transmission of human viruses to horses and vice versa.…”
Section: Neugc␣2mentioning
confidence: 99%
“…There is compelling evidence for the transmission of human viruses to pigs (Kundin, 1970;Mancini, 1985;Tumova et al, 1980;Wibberley et al, 1988) but the information on avian influenza viruses is less comprehensive, although H1N1 viruses in European pigs have possibly originated from birds (Scholtissek et al, 1983). The available evidence indicates that pigs support replication of some avian influenza viruses (Hinshaw et al, 1981) but the tests to date have been limited to only a few subtypes.…”
Section: -2409 © 1994 Sgm H Kida and Othersmentioning
confidence: 99%